Surfactant-decorated graphite nanoplatelets (GNPs) reinforced aluminum nanocomposites: sintering effects on hardness and wear - Baig, Z. (University of Science and Technology Beijing, 2018)
The exceptional properties of graphene make it ideal as a reinforcement to enhance the properties of aluminum matrices and this critically depends on uniform dispersion. In this study, the dispersion issue was addressed by sonication and non-covalent surface functionalization of graphite nanoplatelets (GNPs) using two types of surfactant: anionic (sodium dodecyl benzene sulfate (SDBS)) and non-ionic polymeric (ethyl cellulose (EC)). After colloidal mixing with Al powder, consolidation was performed at two sintering temperatures (550 and 620°C). The structure, density, mechanical and wear properties of the nanocomposite samples were investigated and compared with a pure Al and a pure GNPs/Al nanocomposite sample. Noticeably, EC-based 0.5wt GNPs/Al samples showed the highest increment of 31 increase in hardness with reduced wear rate of 98.25 at 620°C, while a 22 increase in hardness with reduced wear rate of 96.98 at 550°C was observed, as compared to pure Al. Microstructural analysis and the overall results validate the use of EC-based GNPs/Al nanocomposites as they performed better than pure Al and pure GNPs/Al nanocomposite at both sintering temperatures. © 2018, University of Science and Technology Beijing and Springer-Verlag GmbH Germany, part of Springer Nature.